2019
DOI: 10.3390/catal9030294
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Profenofos and Triazophos Residues in the Chinese Cabbage, Brassica chinensis, Using Ce-Doped TiO2

Abstract: Pesticides have revolutionized the modern day of agriculture and substantially reduced crop losses. Synthetic pesticides pose a potential risk to the ecosystem and to the non-target organisms due to their persistency and bioaccumulation in the environment. In recent years, a light-mediated advanced oxidation processes (AOPs) has been adopted to resolve pesticide residue issues in the field. Among the current available semiconductors, titanium dioxide (TiO2) is one of the most promising photocatalysts. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
2
5
1
Order By: Relevance
“…Much interest to note that the storage of profenofos at 54 2 o C for 70 days showed serious effect on the degradation rate of profenofos and increase the rate of formation of 4-bromo-2-chlorophenol as compared to exposure to sunlight. Our findings are in harmony with (Ali and Lamia, 2018) they reported that profenofos degraded rapidly than chlorpyrifos after exposure to heat and sunlight, also the obtained results compatible with several investigators (Burkhard and Guth, 1979) and (Liu et al, 2019) reported that 4-bromo-2-chlorophenol is the main degradation product of profenofos and it can be formed via photolysis and hydrolysis (Capps et al, 1996).…”
Section: Kinetic Studysupporting
confidence: 93%
See 1 more Smart Citation
“…Much interest to note that the storage of profenofos at 54 2 o C for 70 days showed serious effect on the degradation rate of profenofos and increase the rate of formation of 4-bromo-2-chlorophenol as compared to exposure to sunlight. Our findings are in harmony with (Ali and Lamia, 2018) they reported that profenofos degraded rapidly than chlorpyrifos after exposure to heat and sunlight, also the obtained results compatible with several investigators (Burkhard and Guth, 1979) and (Liu et al, 2019) reported that 4-bromo-2-chlorophenol is the main degradation product of profenofos and it can be formed via photolysis and hydrolysis (Capps et al, 1996).…”
Section: Kinetic Studysupporting
confidence: 93%
“…Results from GC-MS analysis Table 3 detected According to the nature of profenofos chemical structure, it contain O-P bond, this bond easily cleavage leads to the formation of 4-bromo-2-chlorophenol. Profenofos can be easily degraded to 4-bromo-2-chlorophenol m/z 208 by hydrolysis and photolysis and that by cleavage the phosphorothioate ester bond (Burkhard and Guth, 1979;Capps et al, 1996;Zamy et al, 2004 andLiu et al, 2019), also Profenofos can be degraded after storage via hydrolysis and photolysis to form O-ethyl-O-(2-chloro-4-bromo-phenyl)-phosphate m/z, 314 [M + -1] (JMPR, 2008), moreover from analysis of our samples using GC-MS found that the characteristic ion at m/z, 339 was molecular ion of O-(4-bromophenyl) O-ethyl S-propyl phosphorothioate which it can be formed by loss of a chlorine atom from profenofos. * Samples before and after storage stability test analyzed together to reduce the analytical error.…”
Section: Identification Of the Degradation Products Of Profenofos By mentioning
confidence: 99%
“…Our findings are following (Ali and Lamia 2018) they stated that after exposure to heat and sunlight, profenofos degraded quickly than chlorpyrifos, even the results obtained consistent with several investigators (Burkhard and Guth 1979) and (Liu et al, 2019) reported that 4-bromo-2-chlorophenol is the main degradation product of profenofos and it can be formed via photolysis and hydrolysis (Capps et al, 1996).…”
Section: Effect Of Sunlight On Profenofos 72%ec (Customs Workout) and Their Impuritiessupporting
confidence: 91%
“…This bond quickly cleavage contributes to the formation of 4-bromo-2-chlorophenol, depending on the type of the chemical structure of profenofos it contains an O-P bond. Hydrolysis and photolysis and cleavage of the phosphorothioate ester bond will easily degrade Profenofos to 4-bromo-2-chlorophenol this result is in harmony with (Capps et al, 1996;Zamy et al, 2004, Ma et al, 2019and Liu et al, 2019. 4-bromo-2-chlorophenol is the main degradation of the profenofos and it can be formed by photolysis (Ali and Lamia 2018) and biodegradation (Talwar and Ninnekar 2015).…”
Section: Discussionmentioning
confidence: 96%
“…The photoactivity results showed the complete removal of imazapyr destruction after 180 min [ 93 ]. Photocatalytic degradation of profenofos and triazophos residues in the Chinese cabbage using Ce-doped TiO 2 was also studied [ 94 ]. Results showed that degradation efficiency of profenofos and triazophos reached 53.3% and 32.1% after 1 day, respectively.…”
Section: Removal Of Pesticidesmentioning
confidence: 99%